Impact of baseline body mass index status on glucose lowering and weight change during sitagliptin treatment for type 2 diabetics. (October 2016) - Chen, Jung-Fu; Chang, Chih-Min; Kuo, Ming-Chun; Tung, Shih-Chen; Tsao, Cheng-Feng; Tsai, Chia-Jen
Highlights: Sitagliptin efficacy in diabetic subjects with different baseline BMI was evaluated. The decline in HbA1c was greater in normal and overweight than obese subjects. Mean body weight increased significantly over the first nine months of therapy in subjects with normal BMI. Obese subjects had initial lag in HbA1c reduction and greater weight loss compared with normal and overweight subjects. Abstract: Aims: This study was designed to evaluate the efficacy of sitagliptin in Taiwanese diabetic subjects with different baseline BMI status. Methods: This was a single-center, hospital-based, retrospective chart review in subjects ( n  = 1874) with type 2 diabetes who received sitagliptin. Subjects were classified into subgroups depending upon their baseline BMI by Taiwan national weight classification: normal (BMI < 24 kg/m 2 ) ( n  = 504), overweight (BMI: 24–27 kg/m 2 ) ( n  = 615), and obese (BMI ⩾ 27 kg/m 2 ) ( n  = 755). Changes in HbA1c and weight were evaluated over a 12month treatment period. Results: For all three groups, the HbA1c levels declined over the first three months by about 8%, and subsequently plateaued for the next nine months. Obese subjects were slower in reducing HbA1c compared with normal and overweight subjects ( P  < 0.05), but at nine months the reduction was similar across groups. Mean body weight increased over the first nine months of sitagliptin therapy in subjects with normal BMI (57.12–58.30 kg), but there was no change in mean body weight in the overweight group. After three months the obese groups had significantly greater loss in body weight compared with the normal group. Conclusions: Baseline BMI status may influence the reduction of HbA1c levels within the first six months of sitagliptin therapy and affect weight change after three months. Being obese was associated with an initial lag in HbA1c reduction and greater weight loss compared with normal and overweight subjects.